Nebulized hypertonic saline 3% for 1 versus 3 days in hospitalized bronchiolitis: a blinded non-inferiority randomized controlled trial - Gaëlle Beal; Catherine Barbier; Sophie Thoret; Amandine Rubio; Mathilde Bonnet; Roseline Mazet; Anne Ego; Isabelle Pin (BMC, 2019)
Abstract Background The use and optimal duration of treatment with nebulized hypertonic saline (HS) in infants hospitalized for acute bronchiolitis is unclear. The objective was to compare the efficacy of 1 versus 3 days of nebulized 3% HS at 72 h of treatment. We conducted a blinded non-inferiority randomized controlled trial including infants aged less than 12 months old, hospitalized for a moderate bronchiolitis. Methods Nebulisations of 3% HS for 1 day were followed by either the continuation of 3% HS (HS3d group) or switched to 0.9% normal isotonic saline (HS1d group) for 2 days Randomization was performed according to a predefined list with a 1:1 ratio, obtained with a random generator number with blocks.. Main outcome was mean Wang clinical severity score (CSS) after 72 h of treatment. Results One hundred sixteen infants (HS1d n = 59 and HS3d n = 57), were included over two epidemic seasons from 2014 to 2016, but recruitement did not reach the planned sample size. The difference for the Wang CSS score in the HS3d vs HS1d group was 0.71 [IC 90% 0.1; 1.3], above the precluded value of 0.4 set in the protocol defining the non-inferiority of shorter treatment duration. Clinical remission was more rapidly obtained in the HS3d than in HS1d (2.3 ± 1.6 vs 2.9 ± 1.4 days, p = 0.04), with a non-significant tendency for less need of nutritional support and supplemental oxygen in HS3d group. Clinical worsening and treatment intolerance were similar in the 2 groups. Conclusions Despite being underpowered, results seem not to be in favour of reducing the duration of nebulised HS treatment from 3 to 1 day in acute moderate bronchiolitis. Trial registration Clinical trials NCT 02538458, October 2014.